تقييم التجربة الجزائرية في مجال جذب الاستثمار الأجنبي المباشر في ظل تداعيات الأزمة المالية العالمية -دراسة تحليلية- - حدة, رايس; مروة, كرامة (Recherches économiques et managériales, 2014)
الملخص          يعتبر الاستثمار الأجنبي المباشر مدخلا هاما من مداخل التنمية الاقتصادية، حيث ثمة اتفاق على أهميته في النشاط الاقتصادي نتيجة للنجاح الذي حققته بعض الدول في عدة مجالات من جراء الاستثمارات الواردة إليها، ولما قدمته من خدمات الدعم لها في إطار تحقيق المنفعة للبلدين في إنعاش النشاط الاقتصادي، لذا يعد وجود إحصاءات دقيقة حول تدفقات الاستثمار الأجنبي المباشر تتفق مع المعايير الدولية أداة تمكن صانعي السياسات من التقييم السليم لمدى تحقق الأهداف الاقتصادية للدولة خاصة وان هذه الإحصاءات تمثل احد المؤشرات الهامة التي تعكس مدى تنافسية الاقتصاد وقدرته على جذب المزيد من تدفقات الاستثمار الأجنبي المباشر.      وهذا النوع من الاستثمارات يتأثر بالأوضاع الاقتصادية العالمية والمؤشرات الاقتصادية التي تدخل في إطار الاقتصاد الكلي، باعتبارها احد محددات المناخ الاستثماري للدول، فالأوضاع والمستجدات التي حدثت بعد الأزمة المالية العالمية التي نشأت في قلب النظام الرأسمالي عام 2008 ، أثرت على الأوضاع التنموية في مختلف دول العالم، مما أدى إلى تغير خارطة الاستثمارات الأجنبية المباشرة وتباين ردود فعلها فيما بين الدول، كانت الجزائر من الدول الأقل تأثرا بمجرياتها لعدم انفتاحها على العالم الخارجي في المجال الاقتصادي والمالي كثيرا. Abstract       Foreign Direct Investment is an important input of the entrances to the economic development, where there is agreement on its importance in economic activity as a result of the success achieved by some countries in several areas as a result of investments coming to it, and for its support services in the framework of achieving the benefit of the two countries in the recovery of economic activity, So is the existence of accurate statistics on flows of foreign direct investment in line with international standards, a tool that enables policy-makers of the proper assessment of the achievement of economic goals of the state, especially that these statistics represent one of the important indicators that reflect the competitiveness of the economy and its ability to attract more foreign direct investment flows.       This type of investment is affected by the conditions of the global economic and economic indicators within the macroeconomic framework, as one of the determinants of the investment climate of the States, The situation and the developments that have occurred with the emergence of the global financial crisis that occurred in the heart of the capitalist system, have affected the conditions of development in various countries around the world, led to a change map of foreign direct investments and the varying reactions among Countries, Algeria was one of the less affected countries because of its none openness to the outside world both in economic and financial field, and this vulnerability touched some sectors of the economy due to lower export revenues dollar-denominated, as the currency most affected by the result of this crisis